NAVIGATING VICTORIAN CITY SPACE: ARTIFICIALITY IN AUSTEN’S NORTHANGER ABBEY AND GASKELL’S NORTH AND SOUTH - Imansari, Nurul; Hamka, Nurhadi (BASIS (Bahasa dan Sastra Inggris), 2025)
Abstract This research investigates the themes of artificiality and social alienation in Jane Austen's Northanger Abbey and Elizabeth Gaskell's North and South, examining how urban settings in Bath and Milton encapsulate the social complexities of Victorian society during the Industrial Revolution. Employing a comparative literary analysis, grounded in urban and social theory as articulated by experts such as Simmel and Parkins, this study highlights how city spaces both reflect and reinforce societal constraints and individual behaviours. Data was gathered through close readings of the primary texts, supported by secondary sources, and analysed to explore patterns of social interaction and urban influence on character development. The findings reveal how Bath’s societal superficiality shapes Catherine Morland’s experience, while Milton’s industrial harshness impacts characters like Margaret Hale and Mr. Thornton, illustrating the varied ways urban settings foster artificiality and exacerbate social divides. This research contributes to understanding Victorian literature's critique of societal structures, emphasizing the value of authenticity and human connection amid social pressures.